Do Antibiotics Reduce the Incidence of Infections After Percutaneous Endoscopic Gastrostomy Placement in Children?. Issue 1 (July 2020) - Krom, Hilde; van den Hoek, Charlotte M.W.; Benninga, Marc A.; Delemarre, Eveline A.; de Jong, Justin R.; Koot, Bart G.P.; Tabbers, Merit M.; Voogt, Heleen; Kindermann, Angelika
ABSTRACT: Objective: Percutaneous endoscopic gastrostomy (PEG) provides a long-term solution for tube dependency. Pediatric guidelines recommend prophylactic antibiotic treatment (ABT) based on adult studies. Aim: To compare wound infection and other complications in children receiving a PEG with and without prophylactic ABT. Methods: Retrospective study including children 0 to 18 years undergoing PEG placement. Patients with (2010–2013) and without (2000–2010) ABT were compared with respect to the occurrence of wound infection and other complications. Results: In total, 297 patients were included (median age 2.9 years, 53% boys). Patients receiving ABT per PEG protocol (n = 78) had a similar wound infection rate (17.9% vs 21%, P = 0.625), significantly less fever (3.8% vs 14.6%, P = 0.013), leakage (0% vs 9.1%, P = 0.003) and shorter hospital admission (2 vs 4 days, P = 0.000), but more overgranulation (28.2% vs 8.7%, P = 0.000) compared with those without (n = 219). Patients receiving any ABT, per PEG protocol or clinical indication (n = 115), had similar occurrence of wound infection (19.1% vs 20.9%, P = 0.768), fever (7.8% vs 14.3%, P = 0.100) and leakage (3.5% vs 8.8%, P = 0.096), a significantly shorter hospital admission (3 vs 4 days, P = 0.000), but more overgranulation (21.7% vs 8.8%, P =0.003) compared with those without (n = 182). Conclusions: Prophylactic ABT does not seem to reduce the occurrence of wound infection but it might be beneficial with respect to fever, leakage and duration of hospital admission, but not overgranulation. A randomized controlled trial is needed to confirm our results.